Model predictive control of high voltage direct current based on voltage source converter transmission system - Nouir Ahmed; Zebirate Soraya; Chaker Abdelkader (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Model predictive control (MPC) has recently been ranked as one of the best modern technics of control for high voltage direct current (HVDC) based on voltage source converter (VSC) transmission systems, since it is a simple controller, understandable and can be implemented easily, also has a dynamic and fast response. The classic double closed loop PI controller has many disadvantages such as the difficulty in determining the Kp, Ki, and Kd parameters as well as the couplings; It is also less robust against systems with slow dynamics and/or having a complex structure. This paper exposes a model predictive control for a two-level converter. Direct power control on rectifier-side based on model prediction and on the inverter-side AC current control strategy is proposed. The controller utilizes the identified model to anticipate the comportment of the output voltage of every switching state at each sampling frequency. At the next sampling interval, the optimum switching state is applied using the cost function as a reference point. The MPC method was verified by the tools of the MATLAB/Simulink software. The simulation results validate the feasibility and effectiveness of the presented control strategy.